An Optimization of Oregano, Thyme, and Lemongrass Essential Oil Blend to Simultaneous Inactivation of Relevant Foodborne Pathogens by Simplex-Centroid Mixture Design - Luiz Torres Neto; Maria Lúcia Guerra Monteiro; Maxsueli Aparecida Moura Machado; Diego Galvan; Carlos Adam Conte Junior (MDPI AG, 2022)
(1) Background: This study aimed to use the simplex-centroid mixture design methodology coupled with a microdilution assay to predict optimal essential oil (EO) formulations against three potential foodborne pathogens simultaneously through the desirability (D) function. (2) Methods: Oregano (ORE; Origanum vulgare), thyme (THY; Thymus vulgaris), and lemongrass (LG; Cymbopogon citratus) and their blends were evaluated concerning minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for Salmonella enterica serotype Enteritidis, Escherichia coli and Staphylococcus aureus. (3) Results: THY combined with ORE or LG were the most promising EO formulations in inhibiting and killing each bacterium separately. Regarding the simultaneous effect, the optimal proportion for maximum inhibition was composed of 75% ORE, 15% THY, and 10% LG, while for maximum inactivation was 50% ORE, 40% THY, and 10% LG. (4) Conclusion: The multiresponse optimization allowed identifying an EO blend to simultaneously control three potential foodborne pathogens. This first report could be a helpful natural and green alternative for the industry to produce safer food products and mitigate public health risks.